INDUKSI KALUS KACANG TANAH (Arachis hypogaea L.) VARIETAS KELINCI DENGAN PERLAKUAN 2,4-D DAN BAP - Ida Royani; Lalu Zulkifli; Prapti Sedijani (Postgraduate, University of Mataram, 2015)
Callus induction determines the successfulness of micropropagation through somatic embryogenesis. This research was conducted to determine the effect of 2,4-D and BAP on callus induction of peanut (Kelinci strain). Callus induction was done on MS medium, with the observed variables were of initiation time, diameter, texture and color callus. Statistical analysis showed that 2,4-D and BAP affect the initiation time, diameter, texture and color callus. The earliest initiation of callus formation was obtained from MS medium with the addition of 4 mg/L 2,4-D. The diameter of the largest callus obtained from MS medium with the addition of 3 mg/L 2,4-D + 1 mg/L BAP. Callus color were affected by the treatment of 2,4-D and BAP, while callus texture was not affected by these treatmen, in which compact callus texture was not affected by these treatment, in which compact callus texture was observed in all treatments.Keywords: Induction of callus, 2,4-D, BAP, peanuts